On the taxonomic status of Phlebotomus breviductus Barretto, 1950 (Diptera: Psychodidae: Phlebotominae) - de Andrade, Andrey J.; Shimabukuro, Paloma H.f.; Galati, Eunice A.b. (Zootaxa, 2013)
The taxonomic status of Phlebotomus breviductus Barretto, 1950 was evaluated based on the morphological and morphometric analysis of the male holotype described from Fazenda Jerusalém, located in the municipality of Alegre, Espírito Santo state, Brazil. After measuring, drawing and photographing the holotype, we concluded that the head and wing of this specimen belong to Trichopygomyia sp., but that the thorax and abdomen belong to a different species, Nyssomyia umbratilis, with an anomalous gonostylus having five spines. The holotype slide consists of parts of specimens representing two different species, thus P. breviductus is not a valid species.